Penerapan Sistem Ekonomi Hijau dalam Pengelolaan Limbah Tebu Hasil Produksi Gula - Yurianingsih, Aisyah Eka; Auril, Sheryn Alivia; Mahdiyyah, Tsalitsatul; Meylianingrum, Kurniawati (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The green economy system is a positive economic activity that can improve people's welfare by reducing the risk of environmental pollution. Sugarcane is one of the big income in one of the Lamongan areas and in the area there is the largest sugar production factory in Asia, this has the potential for a lot of waste generated from the factory activities. This research aims to find out how sugar cane waste management is in accordance with the Green economy and what impact the establishment of a sugar production factory has on the green economy system and community activities. This research uses a qualitative method that focuses on interviews with parties concerned with the factory and a descriptive approach. The results showed that the factory had successfully treated waste by implementing a green economy system so that the waste flowing into the community did not interfere with community activities and pollute the environment. This research underscores the importance of implementing a green economy system in waste management.